Utilization of the Flexibility of Consumers in Power Systems by Implementation of Demand-Side Management - Katerina Bilbiloska; Aleksandra Krkoleva Mateska; Petar Krstevski (SAEM '22, 2022)
The paper presents demand – side management (DSM) application implemented for household consumers. The presented solution is based on a linear optimization technique (LP) to distribute the use of household appliances given certain constraints. Furthermore, it presents the findings of the performed sensitivity analysis of the solution as well as the potential financial benefits for the customers, given that such a solution is applied.
Keywords: demand side management